2017
DOI: 10.1111/famp.12283
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceived Control and Social Support: Linkages to Change in Parenting Behaviors During Early Adolescence

Abstract: Prior studies have found that parents' perceptions of control over their lives and their social support may both be important for parenting behaviors. Yet, few studies have examined their unique and interacting influence on parenting behaviors during early adolescence. This longitudinal study of rural parents in two-parent families (N = 636) investigated (a) whether perceived control and social support when their youth were in sixth grade were independently or interactively associated with changes in parenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 75 publications
(97 reference statements)
2
18
0
Order By: Relevance
“…Another study indicated that for mothers who experience that they have low control over their lives, social support (i.e. having someone to turn to for support and guidance) was important, as it resulted in better (warmer) parent-child relationships (Lippold, Glatz, Fosco, & Feinberg, 2017). These studies, in addition to this study and the literature on lone mothers, point to the importance of social support for parents, not least lone parents.…”
Section: Loneliness and Exclusionsupporting
confidence: 50%
“…Another study indicated that for mothers who experience that they have low control over their lives, social support (i.e. having someone to turn to for support and guidance) was important, as it resulted in better (warmer) parent-child relationships (Lippold, Glatz, Fosco, & Feinberg, 2017). These studies, in addition to this study and the literature on lone mothers, point to the importance of social support for parents, not least lone parents.…”
Section: Loneliness and Exclusionsupporting
confidence: 50%
“…On the contrary, parents who exercise undue control have a damaging effect on emerging adults’ psychological adjustment, generating more anxiety and depression (Nelson et al., ). This suggests that, unlike during adolescence, during which behavioral control is necessary and rules and limits have been proven to be beneficial (Lippold, Glatz, Fosco, & Feinberg, ), during emerging adulthood it is important for the home environment to stimulate maturity and autonomy, with lower levels of direct control. Indeed, even when emerging adults continue to live in the family home and maintain good family relations (Moreno, ), continuing parental control has a negative effect since it goes against their legitimate need for autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not assess parent social support in our study, recent research shows that parents who reported more social support had more warmth and less hostility towards their children (Lippold et al, 2018). Although the text messages parents received in the study remained static with three text messages each week, parents could choose when they wanted to receive the messages.…”
Section: Discussionmentioning
confidence: 99%